18F-Fluorination Using Tri-Tert-Butanol Ammonium Iodide as Phase-Transfer Catalyst: An Alternative Minimalist Approach - Sandip S. Shinde; Kim-Viktoria Bolik; Simone Maschauer; Olaf Prante (MDPI AG, 2021)
The 18F syntheses of tracers for positron emission tomography (PET) typically require several steps, including extraction of [18F]fluoride from H2[18O]O, elution, and drying, prior to nucleophilic substitution reaction, being a laborious and time-consuming process. The elution of [18F]fluoride is commonly achieved by phase transfer catalysts (PTC) in aqueous solution, which makes azeotropic drying indispensable. The ideal PTC is characterized by a slightly basic nature, its capacity to elute [18F]fluoride with anhydrous solvents, and its efficient complex formation with [18F]fluoride during subsequent labeling. Herein, we developed tri-(tert-butanol)-methylammonium iodide (TBMA-I), a quaternary ammonium salt serving as the PTC for 18F-fluorination reactions. The favorable elution efficiency of [18F]fluoride using TBMA-I was demonstrated with aprotic and protic solvents, maintaining high 18F-recoveries of 96-99%. 18F-labeling reactions using TBMA-I as PTC were studied with aliphatic 1,3-ditosylpropane and aryl pinacol boronate esters as precursors, providing 18F-labeled products in moderate-to-high radiochemical yields. TBMA-I revealed adequate properties for application to 18F-fluorination reactions and could be used for elution of [18F]fluoride with MeOH, omitting an additional base and azeotropic drying prior to 18F-labeling. We speculate that the tert-alcohol functionality of TBMA-I promotes intermolecular hydrogen bonding, which enhances the elution efficiency and stability of [18F]fluoride during nucleophilic 18F-fluorination.